Hiatus resolution in Xitsonga - Vratsanos, Alyssa; Kadenge, Maxwell (Stellenbosch Papers in Linguistics Plus, 2017)
Vowel hiatus is dispreferred in many languages of the world. Xitsonga, an understudied cross-border southern Bantu language spoken in South Africa, Mozambique, Swaziland and Zimbabwe, employs a set of four hiatus resolution strategies: glide formation, secondary articulation, elision and coalescence. Glide formation is the primary repair strategy as it shows a least violation of faithfulness. In glide formation, /i/ and /u/ correspond to [j] and [w], respectively. It is blocked when V1 is preceded by a consonant as this would incur a fatal violation of *Complex. When glide formation is blocked, secondary articulation is the next preferred option. One of the interesting features of Xitsonga is that it allows secondary articulation involving mid-vowels /o e/. OCP is often the trigger for elision, the least preferred strategy. Vowel coalescence can take two forms in Xitsonga: /a + i/ → [e] and /a + u/ → [o], both of which incur a non-fatal violation of Uniformity. When coalescence is blocked due to an impermissible sequence of /a/ and another vowel (excluding /i/ and /u/), the /a/ is elided. We argue that a single constraint hierarchy is responsible for these seemingly disjointed repair strategies. The overall significance of this paper lies in the fact that it is the first consolidated description and formal analysis of vowel hiatus resolution in Xitsonga.